The Small Wars Doctrine of the US Marine Corps and Colonial Experience of the European Powers - S. G. Malkin (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The rapid transformation of the current world order excites renewed interest of the expert community in the phenomenon of empire (as a form of the organization of political life). And since the United States plays a central role in this transformation, the history of the Pax Americana, its formation and development, both at the level of the idea and in the field of real politics is of particular relevance. The author argues that clarification of the role and significance of the colonial background in the projection of US military-political power in the late 19th — early 21st centuries allows for better understanding of the theory and practice of international relations both in the era of ‘high imperialism’ and world wars of the 20th century, and in the context of transition from global colonial empires to nuclear superpowers. It may also be instrumental in addressing the deepening contradictions between advocates of a ‘global leadership’ concept and proponents of a multipolar world during the post-Cold War period. In this regard, the paper examines the works of the US military theorists of the late 19th − first half of the 20th centuries that focused on the colonial experience of the leading European powers, as well as the experience gained from interventions involving the US Army and Marine Corps. Special emphasis is given to the concept of ‘small wars’. Building on a wide array of primary sources, presented both by the works of military experts, direct participants in various counterinsurgency operations in the colonies, as well as by the teaching materials and field manuals of the US Marine Corps, the author traces the evolution of this concept which implied establishment of external management and/or control through military and police measures. This allows the author to restore the historical genealogy of current models of internal security promoted in American foreign policy in conditions of proliferating, protracted, and increasingly hybrid civil conflicts. The author concludes that in the interwar period the US law enforcement agencies pragmatically implemented the relevant experience of global empires in Latin American countries within the framework of the Monroe Doctrine, while regarding European powers as political rivals. It is noted that conflicting imperatives of asymmetric and conventional threats to US national security urge researchers and practitioners to revisit after a post-Vietnam period of neglect the approaches of colonial empires to the conduct of small wars and to adapt them to modern conditions. The findings broaden the understanding of the modern leading powers’ approaches to internal security models transfer, as well as of its limits.